Advancing Halal Creative Industry Exports: Strengthening Advocacy and Codification in HPPA Performance to Boost Indonesia's Economic Growth - Fatchurrohman, M; Takhim, Muhamad; Irhamni, Muhammad Ricza (Mazahib, 2025)
The growing global demand for halal products presents promising opportunities for economic development. However, there are still significant gaps in the standardization of the halal certification process, especially in terms of aligning with the provisions of Islamic law for international export purposes. The role of the Halal Product Process Assistants (HPPA) in establishing credible and Shariah-compliant export standards remains unexplored, posing challenges in integrating halal certification into the global supply chain. This research examines how HPPA can strategically contribute to developing a globally recognized halal certification system that is in line with Islamic law. It also aims to assess the role of Islamic law advocacy and technology in strengthening international halal standards. Using qualitative methods inspired by Spradley's ethnographic approach, this study engaged key informants- recognized experts and stakeholders- through focused, open-ended interviews. The study revealed that Islamic law-based halal certification significantly improves the marketability of halal products globally by fostering consumer confidence and regulatory alignment. HPPA's strategic engagement, legal advocacy, and technological innovation can drive creative economic growth and facilitate the integration of halal products into international markets.